2013
DOI: 10.1007/s11999-013-2991-x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Lymphoma of Bone: A Review of 119 Patients

Abstract: Background Lymphoma of bone is uncommon. As a result of this, many aspects of primary lymphoma of bone (PLB) are controversial: the definition, treatment strategies, response criteria, and prognostic factors. Questions/purposes We sought to determine the following in an analysis from a single center over a four-decade period: (1) 5-year disease-free survival of patients with PLB as well as those with systemic lymphoma with bone involvement; and (2) whether prognostic factors (sex, site of tumor, age) were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 14 publications
3
47
0
5
Order By: Relevance
“…Radiotherapy was established as the standard treatment in earlier years (19,20). However, with the development of highly effective chemotherapy regimens and particularly the advent of novel agents, such as the anti-CD20 monoclonal antibody rituximab, the role of radiotherapy has been increasingly questioned by certain researchers (2,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy was established as the standard treatment in earlier years (19,20). However, with the development of highly effective chemotherapy regimens and particularly the advent of novel agents, such as the anti-CD20 monoclonal antibody rituximab, the role of radiotherapy has been increasingly questioned by certain researchers (2,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The five-year OS rates vary greatly, as demonstrated in clinical trials and retrospective population-based studies (2,9,20,28,29,51,53). In addition, various studies have suggested different prognostic factors, including age (29,50,51,56), gender (10), stage (2), LDH levels (10), lesion range (51) and IPI score (28,56).…”
Section: Discussionmentioning
confidence: 99%
“…Rahmen der Autoimmunerkrankung führt zu erhöhtem Lymphomrisiko [10,9], p < 0,0001). In ähnlichen Untersuchungen wurden auch noch die vaskulitische Purpura, die Lymphopenie und der Nachweis von Kryoglobulinen als Risikofaktoren identifiziert [35].…”
Section: » Lymphoproliferation Imunclassified
“…Bei anderen Non-Hodgkin-Lymphomen (NHL) und auch beim Morbus Hodgkin wurde in Einzelberichten neben Arthralgien und Myalgien auch eine eosinophile Fasziitis, eine Arthritis oder Gelenkinfiltration mit Tumorzellen beschrieben [9,31]. Etwa ein Drittel der Arthritiden lag dabei als Polyarthritis vor, und bei ca.…”
Section: Introductionunclassified
See 1 more Smart Citation